Internal audit as manager of optimization in public services: Seguro Social de Salud del Peru - Huamán Rondón, Liliana Ruth (2020)
Objective: Determine if the internal audit is an important agent that allows to optimize the quality processes of the health services provided by Essalud in Peru. Method: It is a descriptive, transversal, prospective, analytical, correlational and non-experimental design research. A survey on the controls of health services was applied to 384 users of the Edgardo Rebagliati Martins-Lima National Hospital, Guillermo Almenara Irigoyen-Lima National Hospital, and IV Alberto Sabogal Sologuren-Callao Hospital. Results: It was found that the special Internal Audit exams had 57.5% effectiveness of the 2013-2016 study period. Conclusions: We confirm the need to have the audit reports on quality management of the service provided by health entities.